2012
DOI: 10.1111/jeb.12058
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spontaneous mutations on competitive ability

Abstract: Understanding the impact of spontaneous mutations on fitness has many theoretical and practical applications in biology. Although mutational effects on individual morphological or life-history characters have been measured in several classic genetic model systems, there are few estimates of the rate of decline due to mutation for complex fitness traits. Here, we estimate the effects of mutation on competitive ability, an important complex fitness trait, in a model system for ecological and evolutionary genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 45 publications
(41 reference statements)
1
21
0
Order By: Relevance
“…Mutations causing a .10% decline in fitness are unlikely to accumulate in MA experiments employing brother-sister mating (Lynch et al 1999), and selection against these mutations can act either through line extinction or against further accumulation within a line (Schaack et al 2013). We previously demonstrated that lines that went extinct during the experiment were phenotypically distinct from extant lines (McGuigan and Blows 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Mutations causing a .10% decline in fitness are unlikely to accumulate in MA experiments employing brother-sister mating (Lynch et al 1999), and selection against these mutations can act either through line extinction or against further accumulation within a line (Schaack et al 2013). We previously demonstrated that lines that went extinct during the experiment were phenotypically distinct from extant lines (McGuigan and Blows 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Our findings are an exception to the widely held assumption that nearly all mutations are deleterious (Bataillon, 2003; Keightley & Lynch, 2003). There are other reports of high frequencies of beneficial mutations that are either induced or spontaneous (Hall, Mahmoudizad, Hurd, & Joseph, 2008; Perfeito, Fernandes, Mota, & Gordo, 2007; Schaack, Allen, Latta, Morgan, & Lynch, 2013; Zhang, Azad, & Woodruff, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…If the Marie population harbors an elevated base mutation load, this may lead to an increased rate of change in the phenotype because new mutations are predicted to accumulate faster in more loaded populations (Agrawal 2002;Shaw and Baer 2011). Given that the Marie lines experienced a greater rate of extinction over the course of the mutation accumulation experiment, an indication of higher mutation load (Lynch 1994), and exhibited large reductions in competitive ability (a complex fitness trait) as a result of mutation accumulation relative to Klamath Lake (Schaack et al 2012), the possibility of high mutation load in this population is plausible.…”
Section: Discussionmentioning
confidence: 99%
“…If the Marie population harbors an elevated base mutation load, this may lead to an increased rate of change in the phenotype because new mutations are predicted to accumulate faster in more loaded populations (Agrawal 2002;Shaw and Baer 2011). Given that the Marie lines experienced a greater rate of extinction over the course of the mutation accumulation experiment, an indication of higher mutation load (Lynch 1994), and exhibited large reductions in competitive ability (a complex fitness trait) as a result of mutation accumulation relative to Klamath Lake (Schaack et al 2012), the possibility of high mutation load in this population is plausible.Alternatively, the elevated rate of change in clutch size in Marie may reflect a difference in genotype · environment interactions between the populations. In the current study, all MA lines were assayed in the same benign laboratory environment, but this environment may represent different levels of stress for animals orginating from the Marie vs. Klamath Lake populations (Baer and Lynch 2003).…”
mentioning
confidence: 99%